The Children with Attention-Deficit/Hyperactivity Disorder (ADHD) More Likely Creates to Irritable Bowel Syndrome (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research aimed study the children with attention-deficit/hyperactivity disorder (ADHD) more likelyCreates to irritable bowel syndrome at Ibn-Rushd Psychiatric Teaching Hospital in Baghdad city, findout the relationship between demographic characteristic, irritable bowel syndrome and Attention-Deficit/Hyperactivity disorder patients. A purposive (non-probability), the sample included (100) patients, from(3-11) years old. A descriptive study carried out from December 10th 2018 to the February 25th 2019, fromfamily Attention-Deficit/Hyperactivity Disorder outpatients of Ibn-Rushd Psychiatric Teaching Hospitalin Baghdad city. A questionnaire was constructed for the purpose of the study, which was a consisted of(2) part. The 1st part included the demographic characteristics and the 2nd part included the items relatedwith irritable bowel syndrome. Data were analyzed through descriptive statistical approach (frequencyand percentage) and inferential statistical approach (correlation coefficient). Scores, Perpson, lycart scaleanalysis that include, t-test, and stepwise multiple regression. The result of the study confirmed that themean of score for the age of sample was (7.1) year, most of them male urban, low score for socio-economicstatus, strong positive to irritable bowel syndrome.